THE INFLUENCE OF RELIGIOSITY, MOTIVATION AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT THE HUMAN RESOURCES DEVELOPMENT AND PERSONNEL AGENCY OF EAST LUWU REGENCY - Arif Gunawan; Suhardi M Anwar; Hadi Pajarianto; Ilham Tahier, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
BKPSDM Luwu Timur Regency as an institution responsible for human resource development at the local government level, requires a deep understanding of the factors that influence employee performance. The purpose of the study was to identify and analyze the influence of religiosity, motivation, and work environment on employee performance at BKPSDM Luwu Timur Regency. This study is a quantitative study with a population of BKPSDM Luwu Timur Regency employees. The sampling technique used saturated sampling so that the number of samples was 54 people. Data were collected using a questionnaire and analyzed inferentially using the help of the SmartPLS statistical tool. The results of the study showed that religiosity had a positive but not significant effect on employee performance. Motivation had a positive and significant effect on employee performance. The work environment had a positive and significant effect on employee performance. Religiosity, motivation, and work environment simultaneously had a positive and significant effect on employee performance. Overall, the partial and simultaneous effects of religiosity, motivation, and work environment emphasize the importance of a holistic approach in human resource management. By paying attention to and optimizing these three factors, BKPSDM Luwu Timur Regency can improve employee performance significantly and sustainably.